High-performance work systems and innovation in Vietnamese small firms. (November 2019) - Do, Hoa; Shipton, Helen
This article examines the interplay between high-performance work systems (HPWS) and the innovation of Vietnamese small and medium sized enterprises (SMEs). Our conceptual model relies on the componential theory of creativity along with HPWS, learning goal orientation (LGO), and creativity and innovation to hypothesise both mediation and moderation mechanisms linking such a relationship. Using a sample of 133 SMEs, we find that (a) employee creativity mediates the pathway between HPWS and firm innovation and (b) LGO moderates the HPWS–employee creativity relationship. This article casts new light on the theoretical mechanism through which HPWS influence firm innovation and add to the understanding of HPWS within SMEs placing employees at the centre of debate.